Germline BRCA testing in Denmark following invasive breast cancer: Progress since 2000 - Aleksandar M. Kostov; Maj-Britt Jensen; Bent Ejlertsen; Mads Thomassen; Caroline Maria Rossing; Inge S. Pedersen; Annabeth H. Petersen; Lise Lotte Christensen; Karin A.W. Wadt; Anne-Vibeke Lænkholm (Acta Oncologica)
Background and purpose: Despite advancements in genetic testing and expanded eligibility criteria, underutilisation of germline testing for pathogenic variants in BRCA1 and BRCA2 (BRCA) remains evident among breast cancer (BC) patients. This observational cohort study presents real-world data on BRCA testing within the context of clinical practice challenges, including incomplete family history and under-referral.